ANALISIS IMPLEMENTASI E-BUDGETING DALAM MENDUKUNG TRANSPARANSI PADA PEMERINTAH KOTA SURAKARTA - Sulistyo Arini; Suci Nasehati (LPPM Politeknik Pratama, 2022)
The implementation of E-Budgeting in financial transparency is one of the advancements in a sound financial governance system. In the context of implementing E-Budgeting and increasing budget transparency, which is the main goal of the Surakarta City Government. Data collection methods include reading the Surabaya city government website and reading relevant literature. The results show that E-Budgeting plays a role in promoting budget transparency in Surakarta City. The Surakarta City Government has implemented budget transparency website services, such as e-budget.surakarta.go.id and ppid.surakarta.go.id, as part of its commitment to open government. The Surakarta City Government also offers ULAS as a way to respond to public expectations and complaints. The Supreme Audit Agency has recognized Surakarta City for twelve consecutive years for excellent financial management by awarding them the title of Unqualified. Publicizing the planning, E-Budgeting, and program activities of the City of Surakarta is one example of the government's commitment to transparency.